2002
DOI: 10.1161/hy0202.104399
|View full text |Cite
|
Sign up to set email alerts
|

Renal Hemodynamic Control by Endothelin and Nitric Oxide Under Angiotensin II Blockade in Man

Abstract: Abstract-To investigate whether endothelin-A receptors and nitric oxide modulate renal hemodynamics in man under angiotensin II receptor-1 blockade, 6 healthy volunteers, on a 240 mmol Na diet, underwent 4 separate renal hemodynamic measurements, in 3 of which endothelin-A blocker BQ-123 0.2 nmol ⅐ kg ⅐ min Ϫ1 was infused for 90 minutes after pretreatment with either placebo, telmisartan 1 mg ⅐ kg ⅐ day Ϫ1 for 3 days, or telmisartan as well, but with co-infusion of both BQ-123 and N G -nitro-L-arginine methyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…11 This same group also provided evidence for ET A -dependent increases in renal vascular resistance in human subjects during AT 1 receptor blockade. 12 Together, these data indicate that regulation of the renal ET system by Ang II may be an important factor in mediating the renal and hypertensive effects of Ang II via stimulation of the ET A receptor. A similar relationship between the renin-angiotensin system and ET in postmenopausal hypertension has recently been reviewed elsewhere.…”
Section: Et-1 In Ang II Hypertensionmentioning
confidence: 79%
“…11 This same group also provided evidence for ET A -dependent increases in renal vascular resistance in human subjects during AT 1 receptor blockade. 12 Together, these data indicate that regulation of the renal ET system by Ang II may be an important factor in mediating the renal and hypertensive effects of Ang II via stimulation of the ET A receptor. A similar relationship between the renin-angiotensin system and ET in postmenopausal hypertension has recently been reviewed elsewhere.…”
Section: Et-1 In Ang II Hypertensionmentioning
confidence: 79%
“…The ET and renin-angiotensin systems are known to interact (4), and an in vivo synergistic effect between ETA receptor antagonism and ACE inhibition has been demonstrated in animals (12) and between ET receptor antagonism and angiotensin AT1 receptor antagonism in humans (37). We have shown, in healthy men who were subjected to systemic ACE inhibition with a clinically relevant dose of enalapril, that the effects of ETA receptor blockade on systemic hemodynamics are enhanced.…”
Section: Discussionmentioning
confidence: 91%
“…Montanari et al (37) demonstrated that ETA receptor antagonism can produce renal hemodynamic changes under conditions of angiotensin AT1 receptor blockade and that this action is inhibited by NO synthase inhibition. We demonstrated a similar synergy between ETA receptor antagonism and ACE inhibition, again dependent on NO, but extended this work by showing that this synergistic effect is abolished, for all indices studied, when the ETB receptor is blocked, suggesting that the ETB receptor is crucial to the mechanism of this interaction.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] Furthermore, we have shown recently that acute ET A receptor antagonism can reduce proteinuria by an additional Ϸ30% on top of that achieved with optimal treatment with inhibitors of the renin-angiotensin system in subjects with proteinuric CKD. 14 The current study suggests that these effects are maintained longer term and are of a similar magnitude.…”
Section: Discussionmentioning
confidence: 99%